A Voyage to England: Containing Many Things Relating to the State of Learning, Religion, and Other Curiosities of that Kingdom - Sorbière, Samuel; Graverol, M.; Sprat, Thomas 1713 (J. Woodard, 1709)
This book is an English translation of the French original, written in 1664. Written after Monsieur Sorbière (1615-1670) spent three months in 1663 in England, this book details his thoughts on several different topics. During his travels he had the opportunity to meet with many well-known scientists and physicians. The first section includes a memoir of his life, written by Mr. M. Graverol. The second section is that of Sorbière's observations on his travels through England. This section contains a plate of a mathematical representation of a "Model of a Floor." The third section is Thomas Sprat, the Royal Society's historian's, thoughts on Sorbière's observations, written to Dr. Wren, Professor of Astronomy at Oxford University. The final section is a letter from Monsieur Sorbière to Monsieur de Courcelles at Amsterdam regarding the Anglo-Dutch War of 1652-1654. The book also contains several one to two page sections of letters to the reader. The original observations were adressed to King Louis XIV with an aim to influence him to support a French academy of science. It is an often critical account that gives a view into England's intellectual life at the time. Thomas Sprat's observations show his sensitivity to Sorbière's work and attacks the thoughts Sorbière presents. This edition notably contains a mistake in the printing: page 109 is printed as 190. The entire work has been digitized.
Keywords: Travel; Voyages and travels; Travelers; Great Britain; England--London; Netherlands--Holland (Province); England; Religion and science; Religion; Curiosities and wonders; Sorbière, Samuel, 1615-1670; Sprat, Thomas, 1635-1713; Anglo-Dutch War (1652-1654); Science--Study and teaching; Louis XIV, King of France, 1638-1715; Letter